Characteristics of Autonomic Dysfunction in Parkinson’s Disease: A Large Chinese Multicenter Cohort Study - Zhou, Zhou; Zhou, Xiaoting; Zhou, Xiaoxia; Xiang, Yaqin; Zhu, Liping; Qin, Lixia; Wang, Yige; Pan, Hongxu; Zhao, Yuwen; Sun, Qiying; Xu, Qian; Wu, Xinyin; et al. (Frontiers in Aging Neuroscience, 2021)
Autonomic dysfunction (AutD) is one of the non-motor symptoms (NMSs) in Parkinson’s disease (PD). To investigate the prevalence and clinical features of AutD in Chinese PD patients, a large multicenter cohort of 2,556 individuals with PD were consecutively recruited to the Parkinson's Disease & Movement Disorders Multicenter Database and Collaborative Network in China (PD-MDCNC) between January 1st, 2017, and December 31st, 2019. The assessment of AutD was performed by Scale for Outcomes in Parkinson's disease for Autonomic symptoms (SCOPA-AUT). The evaluation of motor symptoms and other NMSs were performed using well-established scales recommended by the Movement Disorder Society. We found that out of 2,556 PD patients, 2,333 PD patients (91.28%) had AutD. Compared to the group of PD patients without AutD, the group of PD patients with AutD had older age, older age of onset, longer disease duration, more severe motor symptoms, motor complications, and more frequent NMSs. As for partial correlation analysis, the total SCOPA-AUT score was significantly and positively associated with motor severity scales (UPDRS total score) and some of the NMSs (Rapid Eye Movement Sleep Behavior Disorder Questionnaire (RBD), Epworth Sleepiness Scale (ESS), HAMD (Hamilton Depression Scale), Fatigue Severity Scale (FSS), PDQ (Parkinson’s disease questionnaire). PDSS (PD Sleep Scale) was significantly and negatively correlated with AutD. With logistic regression analysis for potential related factor, age, UPDRS total score, RBD, hyposmia, depression, fatigue may be associated with PD AutD. In conclusion, our multicenter cohort study reported the high prevalence of AutD in Chinese PD and revealed the associated factors of PD AutD.